“Incidencia de las tic en la innovación docente de la escuela de educación básica “Mercedes Cobo de Holguín” - Curay Changoluisa, Elsa Maribel (2023)
Information and communication technologies (ICT) are the most widely used resources to carry out teaching processes through technological elements. Thus, educational institutions seek to achieve excellence in the teaching-learning process by applying these tools. When students learn through these programs, they develop skills and become more investigative. For this reason, the objective of this research is to determine the incidence of information and communication technologies in the teaching innovation of the “Mercedes Cobo de Holguin” basic education school, in such a way that this work has a qualitative and allowed knowing the importance of the application of technologies in the educational process in order to contribute to the development of knowledge. On the other hand, observation, survey and interview were applied as instruments, where the results allowed to identify the influence of technology as a pedagogical aid for students to learn satisfactorily and for teachers to achieve the proposed objectives.